Turkey's accession process to the EU: The agenda behind the agenda - Heinz Kramer (Stiftung Wissenschaft und Politik (SWP), 2009)
The 'Progress Report' on Turkey's efforts on its way to accession, published by the European Commission on October 14, is mostly a routine step in a highly ritualized political process. It deals with the obvious and hardly touches upon the issues of the 'agenda behind the agenda.' These are political factors such as an almost total breakdown of the functioning of the mechanism of 'conditionality-compliance' that is central to any granting of accession; or the intricacies of the Cyprus issue beyond the question of the application of the Additional Protocol; or a far-reaching reconceptualization of Turkish foreign policy, including accession policy, under the AKP government. All of them are as crucial for the final outcome of the accession process as the ongoing 'technical' negotiations about the adoption of the acquis communautaire or the fulfillment of the Copenhagen criteria. The vicious circle that these negotiations are in can only be broken if more attention is paid to this 'second agenda' by both sides
Keywords: 320